(untitled) - Abegglen, James C. (New York, 1985)
Widely acclaimed as the best book yet on Japanese management by two experts, this important book offers a tough-minded analysis of Japanese business methods and competitive strategies.
Keywords: Industrial management,Business planning,Quản lí công nghiệp,Kế hoạch kinh doanh; Japan,Japan,Nhật Bản,Nhật Bản